Optimizing academic library services in the digital milieu : digital devices and their emerging trends - Ryan, Brendan (Chandos information professional series., 2013)
The digital is the new milieu in which academic libraries must serve their patrons; but how best to utilize the slew of digital devices and their surrounding trends? Optimizing Academic Library Services in the Digital Milieu identifies best practices and strategies for using digital devices (such as tablets, e-readers, and smartphones) and copyrighted materials in academic libraries. Special consideration is given to e-books, iBooks, e-journals, and digital textbooks. This title describes how academic libraries can remain current, nimbly addressing user needs. An introduction gives an overview of technology in academic libraries, including the foundations of copyright law and user behavior in relation to digital content. Three parts then cover: digital rights management (DRM); practical approaches to e-content for librarians; and emerging pedagogy and technology. Finally, the book concludes by telling libraries how to remain agile and adaptable as they navigate the digital milieu.